Customers’ perception on Islamic crowdfunding as a possible financial solution for the andemic Covid 19 crises in Malaysia - Abdul Razak, Dzuljastri; Zulmi, Syamsu Rizal; Dawami, Qosdan (2020)
The Covid 19 pandemic has brought an unprecedented crisis globally and people are still struggling for solutions to deal with the crisis. The effect is very broad based be it on social, economics and healthy way of living. The purpose of this study is to investigate customers’ perception on Islamic Crowd Funding (ICF) as a possible financial solution for the pandemic crises. Several factors were used such as concept, justice and fairness and acceptance of ICF. A total of 322 responses were collected by means of questionnaires and processed using SPSS. The result indicated that justice and fairness values has a higher attraction that concept. Hence practitioners should emphasis on these values to attract customers during this Covid 19 crisis. The result of this study further contributed to new body of knowledge on ICF as a solution to the pandemic Covid 19 crisis.